Procedural sedation analgesia in emergency department : survey on knowledge and practice among non-anaesthetic doctors in Hospital Universiti Sains Malaysia (HUSM) - Hamzah, Nazirah (2016)
Background: Procedural Sedation and Analgesia refers to a technique of administering sedatives with or without analgesia to induce a state allowing patients to tolerate unpleasant procedures while being hemodynamically stable. Objectives: This study intended to identify the level of knowledge and practice of procedural sedation and analgesia among two subgroups of non- anaesthetic doctors; medical and surgical based. By comparing the mean of knowledge and practice level between these two major subgroups, demographic factors that influence the knowledge level will also be determined. Methodology: This is a prospective cross sectional study involving 144 non anaesthetic doctors involved in procedural sedation and analgesia in the emergency department HUSM. A questionnaire survey were conducted among equally distributed respondents from two subgroups which is medical and surgical based. This study was conducted from January 2013 to December 2014. Results: The total of 144 respondents aged from 24 to 37 years old with mean age of 30 years old. Mean score of knowledge level in PSA for medical-based doctors is 8.06 compared to 6.60 marks of those in surgical based. There was no significant difference between knowledge level of PSA among medical-based (p value 0.299) and surgical-based (p value 0.233) non anaesthetic doctors in HUSM. Medical based doctors displayed significantly better practices by being aware of protocol available, completing vital signs monitoring, and having formal teaching prior to handling drugs for PSA (p value <0.01). Age, level of education and service years gave positive correlation towards level of knowledge (0.5-0.64). Conclusion: There was no significant difference of knowledge level between medical based and surgical based non anaesthetic doctors in HUSM though both groups revealed more than average knowledge level. Medical based doctors displayed significant good practices in performing procedural sedation analgesia. Older age, higher level of education, and longer service years contributed to higher knowledge level in procedural sedation and analgesia.